Академик Петър Динеков и младият полски българист Едвард Можейко (епистоларни свидетелства от 60-те години на ХХ век) - Иванова, Мая (Poznańskie Studia Slawistyczne, 2020)
The article presents hitherto unknown letters in Polish by Edward Możejko, a Canadian scholar of Polish origin, to the Bulgarian scholar Petar Dinekov. These letters reveal the professional contacts between the two men in the 1960s when the young Możejko defends his dissertation on a topic in the field of Bulgarian studies at the Jagiellonian University and Dinekov is one of his reviewers. The letters are explored in the context of other documentary sources. The present study is part of a larger project on epistolary heritage testifying the active professional contacts of Dinekov with the Polish cultural intelligentsia.